Severity of specific language impairment predicts delayed development in number skills - Durkin, Kevin; Mok, Pearl L. H.; Conti-Ramsden, Gina (Frontiers in Psychology, 2013)
The extent to which mathematical development is dependent upon language is controversial. This longitudinal study investigates the role of language ability in children’s development of number skills. Participants were 229 children with specific language impairment (SLI) who were assessed initially at age 7 and again one year later. All participants completed measures of psycholinguistic development (expressive and receptive), performance IQ, and the Basic Number Skills subtest of the British Ability Scales. Number skills data for this sample were compared with normative population data. Consistent with predictions that language impairment would impact on numerical development, average standard scores were more than 1 SD below the population mean at both ages. Although the children showed improvements in raw scores at the second wave of the study, the discrepancy between their scores and the population data nonetheless increased over time. Regression analyses showed that, after controlling for the effect of PIQ, language skills explained an additional 19% and 17% of the variance in number skills for ages 7 and 8, respectively. Furthermore, logistic regression analyses revealed that less improvement in the child’s language ability over the course of the year was associated with a greater odds of a drop in performance in basic number skills from 7 to 8 years. The results are discussed in relation to the interaction of linguistic and cognitive factors in numerical development and the implications for mathematical education.